Comparison of two different anti-mullerian hormone measurement methods and evaluation of anti-mullerian hormone in polycystic ovary syndrome - Gök Gamze; Bal Ceylan; Seçen Elçin İşlek; Desdicioğlu Raziye; Akbıyık Filiz; Yılmaz Gülsen (Türk Biyokimya Dergisi)
Polycystic ovarian syndrome (PCOS) is a heterogeneous endocrine condition that influences 15–20 % of women at their fertile age. In this academic work, we aimed to research serum anti-mullerian hormone (AMH) levels using the Vidas® and Atellica® methods and other hormone parameters in PCOS.